2013
DOI: 10.1016/j.neuron.2013.02.026
|View full text |Cite
|
Sign up to set email alerts
|

GWAS of Cerebrospinal Fluid Tau Levels Identifies Risk Variants for Alzheimer’s Disease

Abstract: Cerebrospinal fluid (CSF) tau, tau phosphorylated at threonine 181 (ptau) and Aβ42 are established biomarkers for Alzheimer’s Disease (AD), and have been used as quantitative traits for genetic analyses. We performed the largest genome-wide association study for cerebrospinal fluid (CSF) tau/ptau levels published to date (n=1,269), identifying three novel genome-wide significant loci for CSF tau and ptau: rs9877502 (P=4.89×10−9 for tau) located at 3q28 between GEMC1 and OSTN, rs514716 (P=1.07×10−8 and P=3.22×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
321
5
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 343 publications
(371 citation statements)
references
References 56 publications
31
321
5
1
Order By: Relevance
“…Using the same AD biomarkers in CSF as Han et al, Kim et al [54] showed that APOE, LOC100129500, TOMM40, and EPC2 had genome-wide significance. By performing so far the largest GWAS using AD biomarkers in CSF, Cruchaga et al [55] revealed the association of GLIS3 and TREM with AD.…”
Section: Ad Biomarkers From Neuroimaging and In Fluids As The Phenotypementioning
confidence: 99%
“…Using the same AD biomarkers in CSF as Han et al, Kim et al [54] showed that APOE, LOC100129500, TOMM40, and EPC2 had genome-wide significance. By performing so far the largest GWAS using AD biomarkers in CSF, Cruchaga et al [55] revealed the association of GLIS3 and TREM with AD.…”
Section: Ad Biomarkers From Neuroimaging and In Fluids As The Phenotypementioning
confidence: 99%
“…3,4 Enigmatically, despite strong genetic links to tau, CSF tau levels are normal or low in other tauopathies such as PSP and some tau gene (MAPT) mutation carriers. 5,6 The recent development of an ultrasensitive assay for tau in peripheral blood makes it feasible to study the relationship between peripheral tau concentrations and tauopathies.…”
mentioning
confidence: 99%
“…3,4 Here, we hypothesized that plasma tau, similar to CSF tau, may constitute a suitable endophenotype for identifying genetic risk factors for tauopathies. Within this context, we conducted a GWAS for plasma tau level and identified a single nucleotide polymorphism (SNP) (rs242557) within the MAPT gene that showed a genome-wide significant association with plasma, but not CSF, tau levels.…”
mentioning
confidence: 99%
“…Another genome-wide association study that used CSF Tau levels as an endophenotype of LOAD identified novel risk variants of the disease, including SNAR-I, GLIS3 and TOMM40, and confirmed the association of APOE and TREM2 with the variability of CSF Tau and phosphoTau levels 36 . These studies clearly indicate that common genetic variants have an impact on the CSF levels of Tau and that this may be associated with the risk of LOAD or rate of disease progression.…”
mentioning
confidence: 77%